If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ax + -1c = bx + 5c Solving ax + -1c = bx + 5c Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add 'c' to each side of the equation. ax + -1c + c = bx + 5c + c Combine like terms: -1c + c = 0 ax + 0 = bx + 5c + c ax = bx + 5c + c Combine like terms: 5c + c = 6c ax = bx + 6c Divide each side by 'x'. a = b + 6cx-1 Simplifying a = b + 6cx-1
| -12-24d=3(a-15) | | 6x-25=x+34 | | 39=-2x+7x-1 | | 15x^2-17xy-4y^2=0 | | (m+7)*3=(m-3)*4 | | -16+a=-14 | | 3(z-1)-4(5-z)=2(6+z) | | 8x+2=7x(x-4)+5 | | 17+10x=2x+5-4x | | (m+7)*3=(m-3)*5 | | -2x^0= | | 1+4(3-5x)=4x+37 | | 7x=-41 | | -5x-7-x=-19 | | 4x/3-6=14 | | -6-7(k-6)=31-8k | | 4(3-2x)+4x=-4 | | 3(5x-6) | | 4y-4=y-16 | | 3t+1= | | C-7.88=9.25 | | -1+5(2n-2)=31+3n | | 3(2a+3)-4(3a-b)=15 | | 6(4x–3)–10x=14x-15 | | -158-7x=4x+51 | | 4(6n+9)-10= | | w2+36=12w | | 8(y-20=4Y | | 7+m=(m-3)+10 | | 2(1+7p)=8p-40 | | -12=4(u-2) | | t^2+1= |